EXPERTISE IN PRIVATE LAW CASES IN TURKISH LAW - Akcan, Recep; Ercan, Ibrahim (European Scientific Journal, ESJ, 2012)
The issue of the using expertise information to solve a case before the Court is important and the Turkish Law is regulating the issue in details. With the changes made in Code of Civil Procedure (CCP) that took effect on October 1, 2011, new regulations concerning expertise were introduced in order to be implemented in issues related to private law. Regulations regarding expertise were made in articles between 266 and 287 in CCP. Although, there are regulations regarding expertise in other laws apart from CCP, in order not to go beyond the scope of the present study, regulations related to expertise in other laws apart from CCP will not be looked at. The Article is going to explore the issue of the expertise institution in Turkish Civil Procedure Law.